Financial determinants of informal financial development in Sub-Saharan Africa - Simplice Asongu; Valentine B. Soumtang; Ofeh M. Edoh (African Governance and Development Institute (AGDI), 2021)
This study assesses financial determinants of informal financial sector development in 48 Sub-Saharan African countries for the period 1995-2017. Quantile regressions are used as the empirical strategy which enables the study to assess the determinants throughout the conditional distribution of informal sector development dynamics. The following financial determinants affect informal financial development and financial informalization differently in terms of magnitude and sign: bank overhead costs; net internet margin; bank concentration; return on equity; bank cost to income ratio; financial stability; loans from non-resident banks; offshore bank deposits and remittances. The determinants are presented from a plethora of perspectives, inter alia: U-Shape, S-Shape and positive or negative thresholds. The study not only provides a practical way by which to assess the incidence of financial determinants on informal financial sector development, but also provides financial instruments by which informal financial development can be curbed.
Keywords: 330; Informal finance; financial development; Africa